Coronary microvascular dysfunction pathophysiology in COVID‐19. (2nd June 2021) - Yin, Jie; Wang, Shaoshen; Liu, Yang; Chen, Junhong; Li, Dongye; Xu, Tongda
Abstract: Recently, accumulating evidence has highlighted the role of endothelial dysfunction in COVID‐19 progression. Coronary microvascular dysfunction (CMD) plays a pivotal role in cardiovascular disease (CVD) and CVD‐related risk factors (eg, age, gender, hypertension, diabetes mellitus, and obesity). Equally, these are also risk factors for COVID‐19. The purpose of this review was to explore CMD pathophysiology in COVID‐19, based on recent evidence. COVID‐19 mechanisms were reviewed in terms of imbalanced renin‐angiotensin‐aldosterone‐systems (RAAS), systemic inflammation and immune responses, endothelial dysfunction, and coagulatory disorders. Based on these mechanisms, we addressed CMD pathophysiology within the context of COVID‐19, from five perspectives. The first was the disarrangement of local RAAS and Kallikrein‐kinin‐systems attributable to SARS‐Cov‐2 entry, and the concomitant decrease in coronary microvascular endothelial angiotensin I converting enzyme 2 (ACE2) levels. The second was related to coronary microvascular obstruction, induced by COVID‐19‐associated systemic hyper‐inflammation and pro‐thrombotic state. The third was focused on how pneumonia/acute respiratory distress syndrome (ARDS)‐related systemic hypoxia elicited oxidative stress in coronary microvessels and cardiac sympathetic nerve activation. Fourthly, we discussed how autonomic nerve dysfunction mediated by COVID‐19‐associated mental, physical, or physiological factors could elicit changes in coronary blood flow, resulting in CMD in COVID‐19 patients. Finally, we analyzed reciprocity between the coronary microvascular endothelium and perivascular cellular structures due to viremia, SARS‐CoV‐2 dissemination, and systemic inflammation. These mechanisms may function either consecutively or intermittently, finally culminating in CMD‐mediated cardiovascular symptoms in COVID‐19 patients. However, the underlying molecular pathogenesis remains to be clarified.